Microstructure and dielectric properties of compositionally graded Ba1-xSrxTiO3 multilayer tunable capacitors. Issue 4 (April 2021) - Choi, Hyun-Ju; Woo, Jong-Un; Hwang, Hyun-Gyu; Kim, Dae-Su; Sanghadasa, Mohan; Nahm, Sahn
Abstract: Li2 O/B2 O3 -added Ba 1-x Sr x TiO3 (B 1-x S x T) ceramics, where 0.2 ≤ x ≤ 0.35, were well densified at 920 °C with pure perovskite structure. The dielectric constant, tunability, and figure of merit ( FOM ) of B 1-x S x T ceramics increased with x because of the decreasing Curie temperature (TC ). The specimen with x = 0.35, whose TC was close to room temperature, exhibited a large tunability of 27.4 % and FOM of 110 at 10 kV/cm. A compositionally graded multilayer (CGML), which was sintered at 920 °C, was fabricated using B 1-x S x T thick films to produce a temperature-stable tunable capacitor, and it evinced a dense microstructure and a continuous interface between the B1-x S x T thick film and the Ag electrode. This CGML capacitor showed a large tunability (51 %) and FOM (150) at 20 kV/cm. It also exhibited stable tunability (17–28 % at 10 kV/cm) at temperatures between 30–90 °C. Therefore, the B 1-x S x T CGML capacitor is a suitable candidate for temperature-stable tunable capacitors.